Analysis of Risk Factors for Pulmonary Function Disorders among Workers at PT X Coal Division, East Kalimantan - Lisa Septiana; Irfansyah Baharuddin Pakki; Akhmad Azmiardi; Ratno Adrianto; Iriyani K.; Ida Ayu Indira Dwika Lestari (GLOBAL HEALTH SCIENCE GROUP, 2025)
Pulmonary function impairment remains a critical occupational health issue among coal industry workers due to prolonged exposure to airborne pollutants. Despite the implementation of occupational health regulations, respiratory disorders continue to be prevalent, leading to decreased work capacity and increased health risks. Identifying key risk factors is essential to developing targeted preventive measures. Objective: This study aims to analyze the relationship between occupational risk factors and pulmonary function impairment among workers at PT X Coal Division, East Kalimantan. A cross-sectional study was conducted on 183 coal division workers selected through cluster random sampling. Data were obtained through structured questionnaires, spirometry tests, and workplace dust level measurements. Multivariate logistic regression analysis was used to determine the most influential factors associated with pulmonary function impairment. The analysis identified significant associations between pulmonary function impairment and a history of other diseases (p = 0.001; OR = 11.709; 95% CI: 2.901–47.257), work tenure of ≥3 years (p = 0.032; OR = 3.319; 95% CI: 1.109–9.934), heavy physical workload (p = 0.036; OR = 2.807; 95% CI: 1.071–7.361), and inadequate personal protective equipment (PPE) usage (p = 0.015; OR = 2.566; 95% CI: 1.205–5.463). Other factors such as age, body mass index (BMI), work location, dust exposure, exercise habits, and smoking were not significantly associated with pulmonary function impairment. Work-related exposures and individual health conditions play a crucial role in pulmonary function impairment among coal workers. Strengthening workplace safety measures, enforcing PPE compliance, and implementing regular health screenings are necessary to mitigate respiratory risks. Ensuring a safer work environment through targeted preventive strategies is essential for protecting workers from long-term pulmonary complications while enhancing occupational health policies in the coal industry.